Kepadatan Populasi dan Intensitas Kerusakan Sexava coriacea L. pada Tanaman Kelapa di Halmahera Barat - Maluku Utara - Mosu, Kristofel R; Siahaya, Victor G; Masauna, Esther D (Universitas Pattimura, 2023)
The purpose of the study was to obtain dense data on the population of Sexava coriacea pests and the amount of damage intensity to coconut plants in West Halmahera, North Maluku. The method used is a survey and interview of farmers, where the sample villages are determined proportionally to the villages with the highest number of coconuts. Determining the level of population density begins by determining each of the two leaf sheaths facing west and east. Counting insects (imago or nymphs) found on predetermined fronds as many as 600 fronds. The extent of damage was obtained by taking five leaf sheaths, for a total of 750 leaf sheaths. The results showed that the insect pest found was Sexava coriacea L. The average dense population of S. coriacea in Kie Ici village ranged from 18-77 nymphs per tree, a total of 325 heads, an average of 1.63 heads per midrib of coconut leaves, Naga village ranged from 4-36 nymphs per tree, a total of 275 heads, an average of 1.38 heads per midrib of coconut leaves, Maritango village ranges from 10-34 nymphs per tree, a total of 200, an average of 1.00 per midrib of coconut leaves. The average percentage of attacks and damage rate in Maritango village was 32.4% (medium), Naga village 42.8% (medium), and Kie Ici village 48.4% (medium). Natural enemies found in the field are spiders (Arachnida), weaver ants (Oecophylla smaragdina), and suuku birds (Centropus goliath Bonaparte).